An Investigation of Teachers’ Challenges on The Aspects of Challenges in Online Learning - Cahayu Sari; Atikah wati; Nasori Effendi (JELLT (Journal of English Language and Language Teaching), 2022)
The unexpected shift in English language teaching from face-to-face classroom interaction to online learning activities using digital platforms has resulted in several challenges for English teachers and students. These challenges include five aspects: online learning platform, designing materials, internet connection, motivating students, and professional development. Three English teachers participated in this research grounded on a qualitative approach with a case study design. The data was collected through a questionnaire and interview adapted from Dambhare (2020) and Korkmaz & Toraman (2020). The results revealed that operating the E-Learning platform, designing, delivering, and developing the material for online learning, and lack of motivation to students and engagement become the primary challenges of online teaching amidst the global pandemic. Additionally, the participants stated that they encountered problems with an unstable internet connection and the need for professional development programs about ICT integration. The result also shows that the teachers were unfamiliar with the mandatory application for teaching. They still need a guide to learn the application. The impact of this situation is that the teachers should improve themselves to learn more about the technology and find their teaching solutions.